The lifetime experience of traumatic events is associated with hair cortisol concentrations in community-based children. (January 2016) - Simmons, Julian G.; Badcock, Paul B.; Whittle, Sarah L.; Byrne, Michelle L.; Mundy, Lisa; Patton, George C.; Olsson, Craig A.; Allen, Nicholas B.
Highlights: First available study of hair cortisol and lifetime trauma in children. Children's lifetime trauma exposure predicted elevated hair cortisol concentrations. Effects of sex, age, recent stress, depressive symptoms and BMI were controlled for. Findings support use of hair cortisol as a biomarker of traumatic events. Abstract: Adversity early in life can disrupt the functioning of the hypothalamic–pituitary–adrenal axis (HPAA) and increase risk for negative health outcomes. Recent research suggests that cortisol in scalp hair represents a promising measure of HPAA function. However, little is known about the relationship between early exposure to traumatic events and hair cortisol concentrations (HCC) in childhood, a critical period of HPAA development. The current study measured HCC in scalp hair samples collected from 70 community-based children (14 males, mean age = 9.50) participating in the Imaging Brain Development in the Childhood to Adolescence Transition Study (iCATS). Data were also collected on lifetime exposure to traumatic events and current depressive symptoms. Lifetime exposure to trauma was associated with elevated HCC; however, HCC was not associated with current depressive symptoms. Consistent with some prior work, males were found to have higher HCC than females, although results should be treated with caution due to the small number of males who took part. Our findings suggest that hair cortisol may represent a biomarker of exposure to trauma in this age group; however, further study is necessary with a particular focus on the characterization of trauma and other forms of adversity.